Phenomena of radiography science: A scoping review - Törnroos Sanna; Leino-Kilpi Helena; Metsälä Eija (W.B. Saunders Ltd, 2022)
Introduction
The purpose of the study is to clarify the domain of radiography science. The main goal of science is building knowledge and developing ideas and theories that explain, predict, understand or interpret the phenomena investigated. Each discipline has its own perspective to view and study the phenomena of interest. The disciplinary perspective enables researchers in radiography science to reason and conceptualize phenomena, but it can also restrict them. The aim of this review was to investigate phenomena that are at the core of the discipline of radiography science.
Methods
This study used a scoping review as the method. A systematic search was carried out in the databases: Science Direct, Pubmed, Cinahl, and Scopus. The selection of articles was conducted by predetermined inclusion and exclusion criteria for the title, abstract and full text. After the exclusion process, fourteen articles were selected for a final review. The articles were analyzed with inductive content analysis.
Results
From the articles, 117 research interests were identified; these were merged into 17 categories and further into six main categories. The main categories represent the phenomena radiography science investigates. The phenomena are: the radiographers’ profession, clinical practices in diagnostic and therapeutic patient pathways, safe and high quality use of radiation, radiographic technology, discipline, management and leadership of radiography professionals
Conclusions
Radiography science has a conceptual structure of its own that needs more investigation. Radiography science researches distinctive phenomena and specialized knowledge, common to researchers from different traditions and subspecialties thus justifying its existence.
Implications for practice
Investigating the core phenomena of interest in radiography science can support researchers in the field to focus their research and to develop the concepts of radiography.